Modeling the impact of bottom water withdrawal on the dynamics of pesticides in the Kouris dam (Cyprus) - Ma, Shengwei; Kassinos, Stavros; Fatta-Kassinos, Despo; Akylas, Evangelos (My University, 2008)
As part of an effort to understand the water quality dynamics in the Kouris Dam and the impact of possible management strategies, the present study assessed the transport process of atrazine in this reservoir and the effects of bottom and surface withdrawal schemes. The 2- D laterally averaged CE-QUAL-W2 model was used in this study. It was found that, during the period of upstream river discharge, significant vertical variations of atrazine concentrations could be observed in the epilimnion. The maximum concentrations were found at the depth of 5-8m rather than in the surface in this period. This suggests that the widely used assumption of complete mixing in the epilimnion is not valid for this period in this reservoir. It was also found that the dynamics of atrazine in the Kouris Dam were noticeably affected by the withdrawal schemes. Bottom withdrawal would significantly facilitate the transport of pesticides in this reservoir and therefore result in noticeably higher pesticide concentrations in deep layers. However, surface withdrawal is not able to lower atrazine concentrations in the epilimnion in this reservoir possibly due to the decreased mixing depth corresponding to the surface withdrawal, although more atrazine would be removed from the reservoir by the surface withdrawal. These results suggest that it is sensible to integrate withdrawal schemes into reservoir management system to achieve different water quality objectives under various scenarios.
Keywords: Pesticide; Atrazine; Transport; Withdrawal; Simulation; CE-QUAL-W2; Kouris Dam; Stratification; Deep reservoir